Persepsi Budaya Pembelajaran dan Penggunaan Inovasi di Institut Penilaian Negara (INSPEN) - Jamilah, Ahmad Babji (2004)
The purpose of this study is to determine the relationship between organisational members’ perception of the learning culture and its influence on the use of innovation via MS IS0 9000 in INSPEN, which is the subject of the study. INSPEN has implemented MS IS0 9000 and has obtained certification from SIRIM. The Dimension of the Learning Organization Questionnaire (DLOQ) by Watkins and Marsicks (1993, 1996) is used to assess the learning culture. The questions in this study were based on the translation and adaptation of the questions in DLOQ and in the Level of Use by Rebecca (2000) in her study of the Malaysian public sector. The study found that a relationship is positive medium and significance in the seven dimensions in the learning culture ad the use of innovation but it was observed that there was no particular leading factor that showed strong support of such influence. The study also showed that the learning culture in INSPEN is at average level although the use of innovation is at high level. From the aspect of demography, there were no significant differences for the use of innovation and the learning culture. However, for the team learning factor, it was found that there was a difference as to the length of service in which staff with 11 to 15 years of service have a lower team learning culture compared with staff who have served between 1 to 5 years and those with more than 16 years of service. Based on this study several implications can be drawn for submission as an effort towards upgrading the level of the learning culture of the staff of the Valuation and Property Services Department.